A new cheilostome bryozoan from a dinosaur site in the Upper Cretaceous (Campanian) Judith River Formation of Montana. (September 2021) - Taylor, Paul D.; Rogers, Raymond R.
Abstract: Few bryozoans have been described from the Cretaceous Western Interior Seaway (WIS), which is consistent with the low diversity of other typically stenohaline groups in this large expanse of relatively shallow marine water. Here we describe a new cheilostome bryozoan, Conopeum flumineum n. sp., based on well-preserved material from the Campanian Judith River Formation of the Upper Missouri River Breaks National Monument in north-central Montana. The new species shows strong morphological similarities with Conopeum seurati, a Recent species that is often categorized as brackish, but which is euryhaline and can also be found in marine and stenohaline environments. The new Campanian bryozoan species was found in a locality also containing fragmentary remains of dinosaurs and other terrestrial vertebrates, as well freshwater mollusks and terrestrial plant debris. The sedimentology and facies associations of the fossil-bearing site suggest that the depositional setting was a swamp or tidally influenced fluvial backwater on the Judith River coastal plain. The proximity of the site to the western shoreline of the WIS presumably made it susceptible to occasional marine flooding during storms or extreme tides. Previous occurrences of Conopeum in the Cretaceous of the Western Interior have also been associated with dinosaur remains, corroborating the very nearshore and at times even 'upstream' distribution of this euryhaline genus. UUID: http://zoobank.org/bb1fdc8a-5017-44c5-9251-9e24ef3995e3 .